Twitter in the 2019 Indian General Elections: Trends of Use Across States and Parties - Pal, Joyojeet; Panda, Anmol (Economic and Political Weekly, 2019)
Twitter was used widely by various parties, especially political leaders, during the 2019 general election campaign. In this article, a database of 6.9 million tweets is analysed to examine key trends across the parties’ use of social media during election time.